# How do you differentiate #f(x)=1/(16x+3)^2# using the quotient rule?

By signing up, you agree to our Terms of Service and Privacy Policy

To differentiate ( f(x) = \frac{1}{(16x + 3)^2} ) using the quotient rule, follow these steps:

- Identify ( u(x) = 1 ) and ( v(x) = (16x + 3)^2 ).
- Use the quotient rule formula: ( \frac{d}{dx} \left( \frac{u}{v} \right) = \frac{u'v - uv'}{v^2} ).
- Calculate ( u' = 0 ) and ( v' = 2(16x + 3)(16) ).
- Apply the quotient rule formula to find the derivative of ( f(x) ).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- If #f(x)= tan2 x # and #g(x) = sqrt(-4x-3 #, how do you differentiate #f(g(x)) # using the chain rule?
- How do you differentiate #f(x)=csc(1/x^2-x) # using the chain rule?
- What is the implicit derivative of #3=e^y-e^(2y) #?
- What is the implicit derivative of #1=tanx-y^2#?
- How do you differentiate #f(x) = (x^2-4x)/(x+1)# using the quotient rule?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7